Pedagogical Competence of Teachers and Online Engagement of Junior High School Students in the New Normal - P. J. D. Mamacos; Louie Resti Rellon (Universitas Tidar, 2023)
Most students are struggling in this new learning method and their engagement in learning math is deemed to be adversely affected due to limited interactions and accessibility in an online mode of learning, thereby affecting their motivation and achievement. Hence, this study looked into the domain of pedagogical competence of teachers that significantly influence students’ online engagement in the new normal. This study utilized non-experimental quantitative research design employing a descriptive-correlation technique to 100 junior high school students of the research locale identified through random sampling method. The research instrument of this study used two sets of questionnaires in accordance with its declared variables. Results of the data were analyzed using Mean, Standard Deviation, Pearson r correlation, and Linear Regression analysis. Descriptive results of the study revealed that teachers’ pedagogical competence and online engagement of the respondents both obtained a high descriptive level. Furthermore, inferential results of the study suggested there is no significant relationship between teachers’ pedagogical competence and online engagement of junior high school students in mathematics. Given these results, it is highly encouraged that the school must have constant teachers’ professional development programs that can strengthen the abovementioned significant pedagogical competence domains affecting the students’ learning engagement.